GE_GERICHTE P/15446/2014 vom 2. Dezember 2014 - GE Cour de justice (2014)
QUALITÉ POUR RECOURIR; PLAIGNANT; INTÉRÊT JURIDIQUEMENT PROTÉGÉ; DOMMAGE DIRECT; DIFFAMATION; CAS BÉNIN | CPP.310; CPP.382; CP.52; CP.47; CP.173